Health related quality of life among hypertensive adults living in rural Vietnam: Results from a cluster-randomised controlled trial - Cuc T. T. Nguyen; Jahnavi Challagonda; Tung S. Ha; Nhi D. Nguyen; Huong T. T. Nguyen; Duc A. Ha; Oanh T. Tran; Phuong K. Nguyen; Van H. Phan; Giang H. Nguyen; Thu H. T. Nguyen; Robert J. Goldberg; et al. (PLoS ONE, 2026)
Background There is a growing burden of hypertension (HTN) among adults living in rural Vietnam, which is associated with reduced health related quality of life (HRQoL). Few community-based interventions have, however, attempted to improve the quality of life in patients with uncontrolled HTN. This study aimed to examine the impact of a multi-component intervention on HRQoL in adults with uncontrolled HTN. Methods This cluster-randomized controlled trial was conducted in sixteen communities (8 intervention and 8 comparison) living in a rural setting in Vietnam (2017−2022). Consenting adults with uncontrolled HTN were enrolled. The comparison arm received training sessions about HTN prevention and management and patient education materials. The intervention arm received information similar to the comparison group and three enhancement components, namely a storytelling intervention, home blood pressure (BP) self-monitoring, and expanded community health worker services. The primary outcome was the differential change in HRQoL over 12-month follow-up period, measured using the 12-Item Short Form Health Survey (SF-12), which generates a Physical Component Summary (PCS-12) and a Mental Component Summary (MCS-12). The total HRQoL score was calculated as the sum of PCS-12 and MCS-12, with higher scores indicating better HRQoL. Results A total of 671 patients were studied; their mean age was 66 years and 55% were women. At the 12-month follow-up, the intervention group showed a significant increase in their PCS-12 with a multivariable-adjusted difference of 4.2 points (95% CI: 2.0–6.4) compared with the control group. While the MCS-12 scores increased for both groups, their differential change over 12 months was not statistically significant (multivariable-adjusted difference: 1.4 points; 95% CI: −0.6; 3.5). Conclusion Our results demonstrate that a multicomponent intervention effectively improved overall HRQoL with a significant impact on physical health-related HRQoL in individuals with uncontrolled HTN. Trial registration ClinicalTrials.gov, Registration number: https://clinicaltrials.gov/study/NCT03590691 , (registration date July 17, 2018)